An Aminocaprolactam Racemase from Ochrobactrum anthropi with Promiscuous Amino Acid Ester Racemase Activity. (10th July 2018) - Frese, Amina; Barrass, Sarah V.; Sutton, Peter W.; Adams, Joe P.; Grogan, Gideon
Abstract: The kinetic resolution of amino acid esters (AAEs) is a useful synthetic strategy for the preparation of single‐enantiomer amino acids. The development of an enzymatic dynamic kinetic resolution (DKR) process for AAEs, which would give a theoretical yield of 100 % of the enantiopure product, would require an amino acid ester racemase (AAER); however, no such enzyme has been described. We have identified low AAER activity of 15 U mg −1 in a homologue of a PLP‐dependent α‐amino ϵ‐caprolactam racemase (ACLR) from Ochrobactrum anthropi . We have determined the structure of this enzyme, Oa ACLR, to a resolution of 1.87 Å and, by using structure‐guided saturation mutagenesis, in combination with a colorimetric screen for AAER activity, we have identified a mutant, L293C, in which the promiscuous AAER activity of this enzyme towardsl ‐phenylalanine methyl ester is improved 3.7‐fold. Abstract : Kinetic resolution : α‐Amino ϵ‐caprolactam racemase (ACLR) from O. anthropi catalyses the racemisation of ϵ‐ACL, but also of phenylalanine amide and phenylalanine methyl ester, the latter an unprecedented substrate for ACLRs. We have determined the structure of Oa ACLR and used this to engineer a mutant with a 3.7‐fold greater activity than the wild type for the amino acid ester racemisation.